THE ROLE OF DESCRIPTIVE GEOMETRY IN CONTEMPORARY SPATIAL VISUALIZATION AND ENGINEERING PROBLEM SOLVING: AN ANALYTICAL REVIEW - Yusubjonov Jonibek Farkhod oglu (Bright Mind Publishing, 2025)
Descriptive geometry, often regarded as the mathematical language of spatial reasoning, plays a foundational role in engineering, architecture, and design disciplines. In the age of advanced modeling tools and digital CAD systems, the significance of traditional descriptive geometry has been questioned, yet it continues to serve as a vital intellectual framework for understanding spatial relationships and visualizing complex forms. This paper presents a comprehensive examination of the enduring importance of descriptive geometry in contemporary technical education and practice, focusing on its applications in three-dimensional visualization, orthographic projections, intersections, developments, and auxiliary views. Through a blend of theoretical analysis and practical examples, the paper demonstrates how mastery of descriptive geometry enhances the ability of engineers and designers to interpret and create precise graphical representations, solve spatial problems intuitively, and transition effectively into digital modeling environments. The research draws on historical evolution, pedagogical strategies, and integration with modern technologies, arguing that rather than being replaced, descriptive geometry has evolved into a cognitive scaffold for spatial intelligence and digital design literacy. This study concludes with recommendations for reinvigorating descriptive geometry education in the 21st century, advocating for its repositioning as both a conceptual and technological bridge between classic engineering drawing and modern 3D visualization tools.
Keywords: Descriptive geometry, spatial visualization, engineering drawing, projection systems, technical education, CAD integration, 3D modeling, visualization skills, orthographic representation.